Scaling up community activism: the role of intermediaries in collective approaches to community energy - Bird, C; Barnes, J (Sheffield Hallam University, 2014)
Intermediary organisations can play a significant role in the changing environment of UK energy, transcending the perceived divides between individual action, activism and top-down policy. This paper discusses a Bristol based action research project which, working with local community energy groups, explored the role of intermediary organisations not just in bringing together learning, providing support and aggregating impact but also in helping to shape stronger local energy action by connecting across and beyond existing activity in ways that put communities first. This approach enabled the development of the ‘Bristol Community Strategy for Energy’, which takes a different approach to the national ‘Community Energy Strategy’ which it preceded. We consider the roles of intermediary organisations in scaling up community activity: linking with policy and supporting shared action to accelerate community responses to energy concerns. We also draw on the underpinning theory before concluding with recommendations to reinforce the maturing and changing local energy landscape.